2001
DOI: 10.1152/ajplung.2001.280.1.l18
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus triggers cell type-specific proinflammatory responses dependent on the autocrine action of IFN-β

Abstract: Resident cells of the respiratory and gastrointestinal tracts, including epithelial and fibroblast cells, are the initial sites of entry for many viral pathogens. We investigated the role that these cells play in the inflammatory process in response to infection with reovirus 1/L. In A549 human bronchial or HT-29 human colonic epithelial cells, interferon (IFN)-beta, regulated on activation T cell expressed and secreted (RANTES), IFN-gamma-inducible protein (IP)-10, and interleukin-8 were upregulated regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Expression profiling analysis of RNA isolated from U266 cells revealed that reovirus treatment induced a strong anti-viral response, which was characterized by interferon (IFN) stimulation (Supplementary Tables 1 and 2). Consistent with prior reports, reovirus exposure induces an IFN-b response (Hamamdzic et al, 2001;Holm et al, 2007;Steele et al, 2011). While IFN production has been reported to decrease viral spread and efficacy, IFNs have also been shown to elicit anti-tumor effects via inhibition of angiogenesis and stimulation of apoptosis (Sidky and Borden, 1987;Taylor et al, 2008;Shmulevitz et al, 2010).…”
Section: Resultssupporting
confidence: 82%
“…Expression profiling analysis of RNA isolated from U266 cells revealed that reovirus treatment induced a strong anti-viral response, which was characterized by interferon (IFN) stimulation (Supplementary Tables 1 and 2). Consistent with prior reports, reovirus exposure induces an IFN-b response (Hamamdzic et al, 2001;Holm et al, 2007;Steele et al, 2011). While IFN production has been reported to decrease viral spread and efficacy, IFNs have also been shown to elicit anti-tumor effects via inhibition of angiogenesis and stimulation of apoptosis (Sidky and Borden, 1987;Taylor et al, 2008;Shmulevitz et al, 2010).…”
Section: Resultssupporting
confidence: 82%
“…IRF-1 has previously been shown to respond to TLR3 stimulation via poly(I:C) treatment in HT29 human intestinal epithelial cells (52). Furthermore, IRF-1 is essential for IFN-␤1 and CXCL10 expression after reovirus infection in human lung fibroblasts (28). This evidence points to a pivotal role for IRF-1 in TLR3 signaling, directly contributing to the upregulation of CXCL10.…”
Section: Activation Of the Tlr3 Pathway Upon Kshv Infection Of Thp-1 mentioning
confidence: 82%
“…IRF-1 is known to exert transcriptional control over CXCL10, TLR3, and IFN-␤1 (16,28), all of which were observed to be upregulated in KSHV-infected monocytes. It is possible that TLR3 activation stimulates IRF-1, which in turn activates both CXCL10 and IFN-␤1, leading to the promotion of the inflammatory response and a positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been shown that T cells will home to the peripheral margin of recurring mammary tumors without infiltrating the tumor proper and that these immuneeffector cells are likely inhibited by the immunosuppressive nature of the tumor microenvironment (38). Promisingly, reovirus has been shown to induce secretion of proinflammatory factors mediating T-cell infiltration in a number of epithelial-derived cancer cell lines (39). It is plausible that a chemokine repertoire may be induced by reovirus infection in the patients of this study and that this provides a platform for overcoming inefficient T-cell homing.…”
Section: Discussionmentioning
confidence: 99%